2008
DOI: 10.37358/rc.08.11.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surfactants in Emulsion Polymerization Polymers by design

Abstract: The determination of an emulsifier�s adsorption properties under conditions similar to those occurring during emulsion polymerization can provide important information to aid in the selection of the most appropriate surfactant for a given system. Results show that the latex particle size is dependent on the strength of emulsifier adsorption (DEads) at the particle/aqueous phase interface and is a function of the polymer polarity. Use of reactive surfactants can improve latex characteristics by reducing the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The polymerization conditions were then further optimized for each EGDMA concentration by an increase in the amount of SDS/CAPS buffer solution from the previously used 4.8 g to 9.6 g per reaction, thereby increasing the ratio of surfactant to monomer. The number of particles and their size, as well as the degree and rate of polymerization are directly dependent on the concentration of the surfactant. , Employing the outlined adjustments, the monomer conversion reaches over 93% at about 60 min for any crosslinking content of the miniemulsions. As a representative example, the monomer conversions for miniemulsions derived from 60 mol % EGDMA at different dilutions are depicted (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerization conditions were then further optimized for each EGDMA concentration by an increase in the amount of SDS/CAPS buffer solution from the previously used 4.8 g to 9.6 g per reaction, thereby increasing the ratio of surfactant to monomer. The number of particles and their size, as well as the degree and rate of polymerization are directly dependent on the concentration of the surfactant. , Employing the outlined adjustments, the monomer conversion reaches over 93% at about 60 min for any crosslinking content of the miniemulsions. As a representative example, the monomer conversions for miniemulsions derived from 60 mol % EGDMA at different dilutions are depicted (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of particles and their size, as well as the degree and rate of polymerization are directly dependent on the concentration of the surfactant. 40,41 Employing the outlined adjustments, the monomer conversion reaches over 93% at about 60 min for any crosslinking content of the miniemulsions. As a representative example, the monomer conversions for miniemulsions derived from 60 mol % EGDMA at different dilutions are depicted (Figure 3).…”
Section: Protocol Development For Polymerization Ofmentioning
confidence: 99%
“…Functional polymer latexes prepared by emulsion polymerization have found applications in many fields, including water-borne coatings, adhesives, and in biomedical applications. In emulsion polymerization, surfactants control the colloidal stability of the latex, the particle size, and surface functionality of the formed particles and have a large influence on the rheology of the latex. , If surfactants are only physically bound to the surface of the latex particles, the surfactants can migrate toward the film interface upon drying and may have a negative effect on final film properties like water sensitivity, wettability, gloss, adhesion, and blocking. Hence, preferably surfactants are used which are chemically bound to the surface of latex particles. In order to avoid the chemically bound surfactants from being buried inside the latex particles or from forming water-soluble polymer chains that may cause bridging flocculation, an ideal reactive surfactant should not be too reactive at the start of the emulsion polymerization, but at the end of the emulsion polymerization all surfactants should have reacted to obtain a stable latex. , Reactive surfactants containing a propenyl end-group display the right reactivity, , and methacrylic oligomers containing these end-groups (called macromonomers in the remainder of this paper) are readily prepared via cobalt­(II)-mediated catalytic chain transfer polymerization (CCTP). It is known that in a copolymerization these macromonomers act as addition–fragmentation chain transfer (AFCT) agents with methacrylates and that the copolymerization results in block copolymers. In a copolymerization with acrylates (and styrene) the mechanism is more complex and ultimately leads to graft copolymers. In earlier work we synthesized methacrylic acid (MAA) macromonomers via CCTP and used these directly in an emulsion polymerization to form in situ amphiphilic copolymers, in a mechanism similar to what is commonly known as polymerization induced self-assembly (PISA). We observed that only in cases in which these water-soluble MAA macromonomers were sufficiently quickly converted into amphiphilic copolymers stable latexes could be produced.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant act to decrease interfacial tension between the monomer and aqueous phase, stabilize them and generate micelles in which monomers emulsified, and nucleation reaction proceed. 11,12 Also proved that the surfactant in emulsion polymerization is mainly function in lowering the interfacial tension, that enables the emulsification of reactive vinyl monomers and the stable colloidal dispersions formation of nanosize polymer particles. Additionally, the surfactant also increases the number of the particle with decrease particle size.…”
Section: Thermal Stabilitymentioning
confidence: 99%